First steps to a clinical research unit for developmental research in paediatric cardiology: conception and progress of the LEADER project (Long Term Early Development Research) in CHD. (May 2019) - Pfitzer, Constanze; Ferentzi, Hannah; Rosenthal, Lisa-Maria; Kramer, Peter; Berger, Felix; Schmitt, Katharina R. L.
Abstract: Objective: We developed the L ong-term Ea rly De velopment R esearch (LEADER) project to investigate the development of children with CHD and/or after cardiopulmonary resuscitation. Both populations are at risk for delays in motor, cognitive, and language development. However, few studies to date have investigated the longitudinal development in these children. Methods: To establish a clinical research unit, we planned three studies: a cross-sectional study in children after cardiopulmonary resuscitation (LEADER-REA Pilot Study), a longitudinal study in children after cardiopulmonary resuscitation, with a focus on evaluating various biomarkers as predictors for developmental outcome (LEADER-CPR study), and a longitudinal study in children with ventricular septal defect, tetralogy of Fallot, or transposition of the great arteries after cardiac surgery (LEADER-CHD study). Results: Implementation of all three LEADER studies was successful and study protocols were conducted as planned. Findings from the LEADER-REA Pilot study have been recently published and data collection for both prospective trials is ongoing. Descriptive analysis of the first 20 assessments of the LEADER-CHD study showed no severe deficits in overall cognitive, motor, and language developments in the children. Conclusions: Children with CHD and/or after cardiopulmonary resuscitation are at risk for developmental delay. Therefore, a detailed developmental assessment is necessary as a pre-requisite for individual developmental support. Our LEADER project has been shown to be feasible in a clinical setting and is the first step towards the establishment of a clinical research unit in our clinic with a focus on longitudinal research.